Production and nutritive value of the available forage of pigeon pea cultivars during dry season - Favoretto, Vanildo; de Paula, Guilherme H.; Malheiros, Euclides B.; Guideli, Claudia (Pesquisa Agropecuaria Brasileira, 1995)
This work was carried out at Boa Esperança Farm, sited in Jeriquara. Northeast of São Paulo State aiming to study seven cultivars of Pigeonpea ( Cajanus cajan (L.) Millsp). Ramdomized blocks design were used in a split-plot scheme studying the following cultivars: Empasc 307, Fava Larga, Branco de Minas, ICPL 304, ICPL 85063, ICPL 270 and LGR 30, being the last four of them of Indian origin. Cultivars were cut three times during the period May-October, 1992. These cuts were done every twelve weeks when leaves, flowers, pods and branches were harvested with diameter equal or smaller than 6 mm; the set of these fractions was considered available forage. Results showed that the cultivars, except Empasc 307, always revealed higher percentage of leaves and, consequently, higher dry matter production of this fraction in relation to total available forage. The available forage production, as well as the crude protein and acid detergent fiber percentage and in vitro dry matter digestibility allow to recominend the LGR 30, ICPL 304, Branco de Minas and ICPL 270 cultivars as the most promising ones for utilization as protein banks to be used during dry season.
Keywords: chemical composition; dry matter yield; leaves; crude protein; digestibility